Fostering transformation and growth in Niger’s agricultural sector - Wouterse, Fleur Stephanie; Badiane, Ousmane (Wageningen Academic Publishers, 2018)
The current publication intends to add to the understanding of the potential role that smallholders and the institutional and market environment play in a sustainable transformation of the agriculture sector in Niger. The first six chapters look at various innovations, factors promoting their adoption and related impacts on smallholders. Chapter 1 describes the farmer managed natural regeneration (FMNR) in Niger as one of the most extensive agro-environmental transformations in Africa. Chapter 2 assesses the determinants and productivity outcomes of the adoption of zaï pits (a soil and water conservation measure) by smallholders. Chapter 3 explores the extent and severity of land degradation and the impact of rehabilitation on food and nutrition security. Chapter 4 analyses the relationship between gender parity, which exists in households where women are as empowered as men, and fertiliser use. Chapter 5 assesses the potential impacts of the development of small irrigation infrastructure on irrigated land allocation, agricultural production and agricultural income for farm households. Chapter 6 reviews the evidence of links between information and communication technologies (ICTs) and outcomes of farm households in Niger. Chapters 7 to 10 analyse price formation and the integration of cereal markets, trade and the agreements governing trade. Chapter 7 uses spatial econometrics to study market integration of cereals in Niger with a special focus on the millet market. Chapter 8 assesses the structure, past trends and prospects of agricultural trade between Niger and the rest of the region and projects changes in traded quantities, both imports and exports, assuming a continuation of current trends in production, population and non-agricultural income. Chapter 9 gives an overview of the trade patterns in terms of commodities, geographical orientation and nature and provides a description of the institutional framework governing Niger’s trade policy. Finally, Chapter 10 delves into one arrangement governing regional trade, the ECOWAS CET and assesses the benefits and costs of a successful implementation of the ECOWAS CET by its fifteen Member States, with a focus on Niger.